Fuzzy ARTMAP Neural Network IDS Evaluation applied for real IEEE 802.11w data base - Vilela, Douglas W. F. L. [UNESP]; Lotufo, Anna Diva P. [UNESP]; Santos Junior, Carlos R.; IEEE (Ieee, 2018)
In the latest years, the network computers and computational systems are receiving several cyber-attacks that affect its security. This issue is pushing researches at intrusion detection system (IDS) techniques development. This paper describes the creation of a real database of a wireless network with IEEE 802.11w security amendment applied. The database was used to evaluate the Fuzzy ARTMAP classifier IDS. The methodology shows the implementation of Fuzzy ARTMAP neural network as IDS. The obtained results are promising and attest that the proposed classifier is feasible for this IDS application.
Keywords: Wireless Network; Information Security; IDS; Database; Fuzzy ARTMAP